Production of muons from heavy-flavour hadron decays in pp collisions at √s = 5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Ohlson, Alice; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Journal of high energy physics, 2019)
Production cross sections of muons from semi-leptonic decays of charm and beauty hadrons were measured at forward rapidity (2.5 < y < 4) in proton-proton (pp) collisions at a centre-of-mass energy s√s \sqrt{s} = 5.02 TeV with the ALICE detector at the CERN LHC. The results were obtained in an extended transverse momentum interval, 2 < pT< 20 GeV/c, and with an improved precision compared to previous measurements performed in the same rapidity interval at centre-of-mass energies s√s \sqrt{s} = 2.76 and 7 TeV. The pT- and y-differential production cross sections as well as the pT-differential production cross section ratios between different centre-of-mass energies and different rapidity intervals are described, within experimental and theoretical uncertainties, by predictions based on perturbative QCD.Open image in new window
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Der Name "Yuncu" [Yüncü] ist in der Verfasserangabe falsch geschrieben
The ALICE Collaboration: S. Acharay, V. Anguelov, M. Arslandok, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, J. Stachel, B. Windelband, A. Yuncu [und 1008 weitere Personen ]
Gesehen am 04.11.2019